The Challenges of women entrepreneurs in the crisis environment in northern province - Theepavathana, T.; Sathana, V. (University of Jaffna, 2024)
Purpose: The purpose of the study is to explore the challenges of women entrepreneurs in the crisis environment in Northern Province. Design/Methodology/Approach: This study was conducted using mixed method approach. Under the qualitative study, data collection was conducted by using interview and focus group discussion among the women entrepreneurs. Coding method was applied to find out the themes. Under the quantitative research, convenient sampling method was applied to select respondents and structured questionnaire was developed and shared with participants to collect data in this study. Exploratory Factor Analysis (EFA) used to find out the determinant factors of women entrepreneurs’ challenges. Findings: This study reveals the five factors that hindering the progress of women entrepreneurs in the Crisis Environment in the Northern Province. Research findings reveled that Culture and gender role are the major challenge of women entrepreneurs in the crisis environment. Business Sustainability, Lack of priorities, Raw materials and Marketing factors are ranked next. Research limitations: There is no uniformity among selected sectors and responses. Lack of statistical information leads to going for convenient sampling rather than random sampling to gain a comprehensive understanding of the research topic; larger sample may provide more significant results. Implications: The study offers valuable information to understand the phenomenon of women entrepreneurs in crisis environment. This research revels considerable implication for decision makers to understand the challenges of women led enterprises in the crisis context in Northern Province.
Keywords: Business sustainability; Culture and gender role; Economic crisis; Marketing factors; Women entrepreneurs